2020
DOI: 10.3389/fmicb.2020.01624
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic Responses of Marine Free-Living Bacterial Community to Phaeocystis globosa Bloom in Beibu Gulf, China

Abstract: Phaeocystis globosa blooms are recognized as playing an essential role in shaping the structure of the marine community and its functions in marine ecosystems. In this study, we observed variation in the alpha diversity and composition of marine free-living bacteria during P. globosa blooms and identified key microbial community assembly patterns during the blooms. The results showed that the Shannon index was higher before the blooming of P. globosa in the subtropical bay. Marinobacterium (γ-proteobacteria), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 64 publications
(87 reference statements)
2
12
0
Order By: Relevance
“…Increasing evidence has shown that disturbance could select species exhibiting speci c biological traits and markedly alter the composition of SCP community (Li et al, 2020;Stegen et al, 2012). A high relative abundance of Thalassiosira, Pseudo-nitzschia and Skeletonema, were observed and widely spread in the heavy eutrophication Maowei Sea, whereas Thalassiosira, Minutocellus, Navicula, and Chaetoceros were signi cantly over-dominated in the Qinzhou Bay and Beibu Gulf open sea as eutrophic states decreased, which is consistent with previous studies (Leruste et al, 2019;Tian et al, 2017).…”
Section: Characteristics Of the Scp Communities With Increasing Eutrophicationsupporting
confidence: 90%
“…Increasing evidence has shown that disturbance could select species exhibiting speci c biological traits and markedly alter the composition of SCP community (Li et al, 2020;Stegen et al, 2012). A high relative abundance of Thalassiosira, Pseudo-nitzschia and Skeletonema, were observed and widely spread in the heavy eutrophication Maowei Sea, whereas Thalassiosira, Minutocellus, Navicula, and Chaetoceros were signi cantly over-dominated in the Qinzhou Bay and Beibu Gulf open sea as eutrophic states decreased, which is consistent with previous studies (Leruste et al, 2019;Tian et al, 2017).…”
Section: Characteristics Of the Scp Communities With Increasing Eutrophicationsupporting
confidence: 90%
“…8b & 8d) that was signi cantly affected by nitrogen concentration, salinity, and temperature. Increasing evidence has shown that disturbance could select species exhibiting speci c biological traits and markedly alter the composition of picophytoplankton community [31,32]. A high relative abundance of Rhodophyta was observed and widely spread in the heavy eutrophication Maowei Sea, whereas Bacillariophyta was signi cantly over-dominated in the Qinzhou Bay and Beibu Gulf open sea as eutrophic states decreased, which is consistent with previous studies [33,34].…”
Section: Assembly Processes Of Picophytoplankton Communities Along Eusupporting
confidence: 87%
“…Further, PO 4 3− and SiO 3 2− were positively correlated with the microbial communities in April and June, and negatively correlated with the communities in March. Indeed, similar temporal variations of FL microbial communities associated with nutrients have been observed (Li et al ., 2020), manifesting the impacts of environmental factors on the succession of the microbial community during P. globosa blooms.…”
Section: Discussionmentioning
confidence: 99%
“…The spatial factors played a slightly stronger role in shaping the total communities (VPA analysis) as a minor proportion (13.01%) of community variation explained by PCNM variables, and similar microbial dispersal limitations between distant environments had also been observed (Zhang et al ., 2014; Jiao et al ., 2017). Moreover, the abundance of P. globosa cells and environmental variables simultaneously accounted for 8.47% of the variation, suggesting that they may be dependent on each other to some extent (Li et al ., 2020). Overall, the biogeography of the total microbial communities was driven by strong environmental selection and weak dispersal‐related processes, and the influence of the P. globosa bloom cannot be neglected.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation